Morphometric and phenotypic characteristics of eight genotypes of Coffea arabica L. during vegetative development - Galarza , María; Valverde, Alfredo (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2025)
Coffee production represents an important source of employment and economic dynamism for the south of the province of Manabí, so it is appropriate to identify the genotypes with the best morphological behaviour. The objective of the research was to evaluate the morphological and phenotypic variables of eight genotypes of Coffea arabica L. ("café arabica") in their third year of vegetative development, in order to identify the best morphological attributes for large-scale multiplication. A total of 348 plants of coffee genotypes Acawa, Catimor, Catucaí, Sarchimor, Bourbon yellow, Bourbon red, Manabi and Catuaí were evaluated. For the statistical analysis of the metric variables, a completely randomised design was used and linear regression, and for the analysis of the phenotypic variables, the chi-square statistical analysis was applied. The results showed highly significant differences (P<0.01) in all quantitative and qualitative variables. The genotype Acawa showed a better response for leaf length and branch length, Manabí 01 had greater petiole length and stem diameter; Catuaí showed greater number of branches, number of nodes and plant height, Bourbon yellow showed greater length between branches and greater internode length. As for the analysis of the qualitative variables, the colour of young leaves, the Bourbon revealed a reddish brown colour, the other genotypes are green; the leaf shape is oval, except for the Sarchimor that showed obovate leaves.